2014
DOI: 10.1097/phm.0b013e3182a92f85
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Hybrid Ankle Foot Orthosis Made of Polypropylene and Fabric in Chronic Hemiparetic Stroke Patients

Abstract: According to the results of this study, the hybrid AFO showed a similar effect in function, except for ankle dorsiflexion angle at heel strike, and was superior with regard to convenience compared with the conventional plastic AFO in chronic hemiparetic stroke patients. Therefore, it seems that, in general, the hybrid AFO can be recommended for hemiparetic stroke patients who require an AFO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…The selected papers were divided according to the body region treated and the main diagnosis underlying orthotic use. Tables 1 and 2 list 99 papers assessing patient satisfaction with site- or region-specific devices (24 for upper limbs (Table 1) 1235 and 75 for lower limbs (Table 2) 39…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected papers were divided according to the body region treated and the main diagnosis underlying orthotic use. Tables 1 and 2 list 99 papers assessing patient satisfaction with site- or region-specific devices (24 for upper limbs (Table 1) 1235 and 75 for lower limbs (Table 2) 39…”
Section: Resultsmentioning
confidence: 99%
“…Negative feelings can reduce compliance to the treatment, limiting orthosis utilization and patient socialization, while positive reactions give useful feedback on orthosis suitability and usability. The two main patient perceptions assessed by the questionnaires were comfort in wearing the orthosis 1014,19,21,23,27,28,31,3540,42,43,47,48,5052,58,64,66,71,72,74,79,80,91,103,106,112,114,115 and orthosis-induced pain. 10,11,24,25,27,32,34,37,38,46,71,76,9092,96,97,99,100,104,107110 Comfort and discomfort (caused by orthosis-induced pain) are in fact two separate entities related to different ...…”
Section: Resultsmentioning
confidence: 99%
“…For each subject, the normalized trials were averaged over the seven trials to get a single representative cycle per subject. Five clinically relevant points of interest were extracted for each representative cycle (Sinclair et al, 2012a;Do et al, 2014;Yu et al, 2013;Gill and O'Connor, 2003): maximal and minimal values, values at heelstrike and at toe off, and amplitude (difference between maximum and minimum) over all the gait cycle. Those variables are classically extracted from gait cycles to analyze gait.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been well established that there are beneficial effects of wearing an AFO on the gait pattern. When stroke patients wear an AFO and walk at self-selected speed, previous studies have reported significant increases in walking speed 2 , 3 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ) , cadence 2 , 3 , 5 , 6 , 7 ) , step length 2 , 3 , 5 , 9 , 13 , 14 ) , step length symmetry 2 , 17 ) , stride length 3 , 6 , 7 , 8 , 9 , 18 ) , single support time 2 , 5 , 19 ) , and a decrease in double support time 2 , 20 ) . The current study confirmed these results for single support time of the affected side, step length of the unaffected side, and double support time of the unaffected side when wearing a Y-tech AFO.…”
Section: Discussionmentioning
confidence: 99%
“…Different study designs were used to test the effects of an AFO. Comparisons of different types of AFOs with the footwear or barefoot walking were used 3 , 5 , 6 , 8 , 16 , 17 , 20 ) . Two studies have compared different subgroups of patients.…”
Section: Introductionmentioning
confidence: 99%